2016
DOI: 10.1152/ajpcell.00168.2016
|View full text |Cite
|
Sign up to set email alerts
|

Chenodeoxycholic acid requires activation of EGFR, EPAC, and Ca2+ to stimulate CFTR-dependent Cl secretion in human colonic T84 cells

Abstract: Bile acids are known to initiate intricate signaling events in a variety of tissues, primarily in the liver and gastrointestinal tract. Of the known bile acids, only the 7α-dihydroxy species, deoxycholic acid and chenodeoxycholic acid (CDCA), and their conjugates, activate processes that stimulate epithelial Cl secretion. We have previously published that CDCA acts in a rapid manner to stimulate colonic ion secretion via protein kinase A (PKA)-mediated activation of the dominant Cl channel, the cystic fibrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 75 publications
0
17
0
Order By: Relevance
“…, ; Domingue et al. ) and others had reported that short‐term (<30 min) bile acid treatment had no effect on TER, we first focused on examining the effect of long‐term (≥18 h) CDCA and LCA on TER. Using the maximal effective concentrations used in our earlier studies (Ao et al.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…, ; Domingue et al. ) and others had reported that short‐term (<30 min) bile acid treatment had no effect on TER, we first focused on examining the effect of long‐term (≥18 h) CDCA and LCA on TER. Using the maximal effective concentrations used in our earlier studies (Ao et al.…”
Section: Resultsmentioning
confidence: 99%
“…; Domingue et al. ) and others (Kelly et al. ) have found that studying signaling cascades in T84 cells in the presence of serum, often leads to inconsistencies in data, due to the undefined and variable composition of serum.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations